Dielectric properties characterization of the rice and rice weevil for microwave heating treatment - Maliki Ibrahim; Rosemizi Abd Rahim; Junita Mohd Nordin; Siti Zulaika Abdul Nyzam; Norzakiah Amira Amatkhri (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the dielectric properties characterization of the rice and rice weevil for microwave heating disinfestation treatment application. Infestations of insects in stored grain have become a major threat to food supply globally. It contributes to damage to the stored grain and had caused economic losses. The current method to control the infestation which is by using chemical fumigation could give harm to human health and cause environmental pollution. The ability of microwave energy to kill the insects using dielectric heating technique has a high potential as an alternative method to control the infestation of the insect. Knowledge of dielectric properties of the insects is important to understand the interactions of the insect with electromagnetic fields. Hence, this paper presents the evaluation of the dielectric constant, and dielectric loss factor, of the insects and grain using open- ended coaxial probe method. The dielectric properties of the rice weevil, S. Oryzae and rice are measured using an open-ended dielectric probe. Found that the dielectric constant, loss factor and loss tangent for both samples are inversely proportional to the frequency.  Knowledge of the moisture content and temperature of the insects and rice is very important to characterize the dielectric properties for future development of microwave heating disinfestation treatment effectively.